2000
DOI: 10.1053/he.2000.5634
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell activation by lipopolysaccharide in rats: Role for lipopolysaccharide binding protein and toll-like receptor 4

Abstract: Lipopolysaccharide (LPS) binding protein (LBP) is a keyEndogenous lipopolysaccharides (LPS) have been implicated as a cofactor in promoting liver injury in many models of liver injury, including alcoholic hepatitis. 1,2 In the Tsukomoto and French model of rat alcoholic hepatitis, 3 the degree of liver injury is diminished by treatment with either antibiotics, lactobacillus, or polymixin, all of which decrease endogenous LPS. 4,5 In this model, Kupffer cells, when activated by LPS, play a prominent role in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
166
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(173 citation statements)
references
References 30 publications
(36 reference statements)
4
166
0
3
Order By: Relevance
“…29 Although our inability to extend the conclusion on LPS response from bone marrow macrophages directly to liver KC represents a limitation, it has recently been shown that KC do express functional TLR4 (including CD14 and MD2) and respond to LPS in a fashion similar to other macrophage populations. 30,31 Conversely, the use of in vitro macrophage/hepatoma cell culture systems broaden the significance of our findings and allowed study of TLR4-dependent events in well-defined liver cell substitutes rather than in native liver cells that have been exposed to prolonged and often harmful ex vivo separation procedures. Although macrophage-hepatoma cell culture experiments support our hypothesis, KC-hepatocyte interactions in vivo still need to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 87%
“…29 Although our inability to extend the conclusion on LPS response from bone marrow macrophages directly to liver KC represents a limitation, it has recently been shown that KC do express functional TLR4 (including CD14 and MD2) and respond to LPS in a fashion similar to other macrophage populations. 30,31 Conversely, the use of in vitro macrophage/hepatoma cell culture systems broaden the significance of our findings and allowed study of TLR4-dependent events in well-defined liver cell substitutes rather than in native liver cells that have been exposed to prolonged and often harmful ex vivo separation procedures. Although macrophage-hepatoma cell culture experiments support our hypothesis, KC-hepatocyte interactions in vivo still need to be evaluated in future studies.…”
Section: Discussionmentioning
confidence: 87%
“…IL-1, IL-6, and TNF-␣ enhance liver TLR2, but not TLR4 expression (10). Functionally, Kupffer cells are capable of responding to LPS stimulation (12). However, whether TLR4 expression in hepatocytes is sufficient to respond to TLR ligands remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…LPS has been reported to increase the plasma LBP level by promoting its synthesis in the liver, intestine, and lung 30 . LBP transfers LPS as LPS/LBP complexes 31 to cell surface CD14 presented on the cells of myeloid lineage 32 , and thus LBP activates monocytes and tissue macrophages 31,33 to produce TNF-α 34 . However, LBP has been reported to induce different responses depending on its concentration in vitro.…”
Section: Discussionmentioning
confidence: 99%